(untitled) (Journal of Hama University, 2025)
The current research aimed to determine the effectiveness of the (KUD) strategy in developing academic achievement in science among fourth-grade students in the city of Hama. The semi-experimental approach was used, and the sample consisted of (64) male and female students distributed (32) male and female students in the first experimental group and (32) male and female students in the second experimental group. An achievement test consisting of (20) multiple-choice items was prepared, and the results showed: The effectiveness of the (KUD) strategy in developing academic achievement and learning retention in science among fourth-grade students. There is a statistically significant difference between the average scores of students in the control and experimental groups in the direct post-application of the achievement test, in favor of the experimental group. There is a statistically significant difference between the average scores of the experimental group students in the direct pre- and post-applications of the achievement test in favor of the direct post-application. There is no statistically significant difference between the average scores of the experimental group students in the direct post-test and the deferred post-application of the achievement test.